A double-sided perovskite solar cell and a method for preparing the same

The preparation of double-sided perovskite solar cells through the plane lifting method solves the problem of uneven film layer, improves the photoelectric conversion efficiency and thickness uniformity, and achieves efficient power generation and cost saving effects.

CN114744130BActive Publication Date: 2025-04-01HUANENG RENEWABLES CORPORATION LIMITED +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210338572.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-01
Publication Date
2025-04-01
Estimated Expiration
2042-04-01

AI Technical Summary

Technical Problem

The film layer of the double-sided perovskite solar cells is uneven during the preparation process, resulting in low photoelectric conversion efficiency and serious system mismatch, making it difficult to meet the needs of efficient power generation and cost saving.

Method used

The double-sided perovskite solar cells are prepared by the plane lifting method. Through the step-by-step plan lifting method, the soaking and lifting process of the composite layer group in the perovskite precursor solution is controlled to form a perovskite active layer with uniform thickness.

Benefits of technology

The thickness uniformity of double-sided perovskite solar cells is improved, the power generation power is enhanced, and the production cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114744130B_ABST
    Figure CN114744130B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of solar cells, and in particular to a double-sided perovskite solar cell and a preparation method thereof. The preparation method comprises: a) sputtering and depositing indium tin oxide on both sides of glass to form a double-sided conductive substrate; b) sputtering and depositing a first charge transport layer on both sides of the double-sided conductive substrate; c) immersing the obtained composite layer group in a perovskite precursor solution at a three-step specific rate for soaking; d) lifting the immersed composite layer group out of the perovskite precursor solution by plane lifting, annealing, and forming a perovskite active layer on both sides of the composite layer group; the lifting process rises at a three-step specific rate; e) sputtering and depositing a second charge transport layer on the surface of the perovskite active layer, annealing; f) sputtering and depositing a conductive electrode on the surface of the obtained second charge transport layer to obtain a double-sided perovskite solar cell. The double-sided perovskite solar cell has excellent thickness uniformity, high power generation and cost saving.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solar cells, and in particular to a double-sided perovskite solar cell and a preparation method thereof. Background Art

[0002] Bifacial modules can effectively increase power generation and reduce system LCOE, and have incomparable advantages over traditional monofacial modules. However, for bifacial modules, it is challenging to prepare bifacial perovskite and transmission layers with uniform film layers at one time. The uneven film layers of bifacial modules result in different overall power outputs of the modules. Usually, the system mismatch of bifacial modules is more than 3 times that of conventional modules, which requires that each film layer be prepared more uniformly. Better uniformity will minimize mismatch losses caused by inconsistencies during system design and string connection to inverters. At present, the one-time immersion and pulling method is commonly used in the preparation of bifacial modules. During the immersion and pulling process, the uniformity of the upper and lower film layers of the glass varies greatly, and the overall photoelectric conversion efficiency is low due to the series structure of the battery. Summary of the invention

[0003] In view of this, the technical problem to be solved by the present invention is to provide a double-sided perovskite solar cell and a preparation method thereof. The double-sided perovskite solar cell prepared by the plane lifting method of the present invention has better thickness uniformity, higher power generation capacity, and saves costs.

[0004] The present invention provides a method for preparing a double-sided perovskite solar cell, comprising the following steps:

[0005] a) sputtering indium tin oxide on both sides of the glass to form a double-sided conductive substrate;

[0006] b) sputtering and depositing a first charge transport layer on both sides of the double-sided conductive substrate;

[0007] c) lowering the composite layer group obtained in step b) at a rate of 14 to 16 mm / s, then at a rate of 7 to 9 mm / s, and finally immersing it in a perovskite precursor solution at a rate of 3 to 5 mm / s;

[0008] d) lifting the immersed composite layer group out of the perovskite precursor solution by plane lifting, annealing, and forming perovskite active layers on both sides of the composite layer group;

[0009] The lifting process includes: firstly rising at a rate of 1 to 3 mm / s, then rising at a rate of 7 to 9 mm / s, and finally rising at a rate of 14 to 16 mm / s;

[0010] e) annealing after sputtering and depositing a second charge transport layer on the surface of the perovskite active layer;

[0011] f) sputtering and depositing a conductive electrode on the surface of the obtained second charge transport layer to obtain a double-sided perovskite solar cell.

[0012] Preferably, in step a), the sputtering deposition method is a vertical magnetron sputtering method;

[0013] The parameters for sputter depositing ITO on both sides of glass include:

[0014] Background vacuum degree <4×10 -4 Pa, target-substrate distance is 15-80 cm, sputtering power is 140-500 W, and the flow ratio of Ar gas to O2 is 30-55:1;

[0015] The thickness of the indium tin oxide deposition is 120 to 200 nm;

[0016] The optical transmittance of the double-sided conductive substrate is 80% to 90%, and the resistance is 5 to 20Ω.

[0017] Preferably, in step b), the sputtering deposition method is a vertical magnetron sputtering method;

[0018] The first charge transport layer is an electron transport layer or a hole transport layer;

[0019] The material of the electron transport layer includes TiO2, ZnO or CdS;

[0020] The hole transport layer is made of NiOx.

[0021] Preferably, the parameters for sputtering and depositing the electron transport layer on both sides of the double-sided conductive substrate include:

[0022] Background vacuum degree <4×10 -4 Pa; target-substrate distance is 10-65 cm, sputtering power is 100-350 W, flow ratio of Ar gas to O2 is 20-75:1;

[0023] The thickness of the electron transport layer is 15-50 nm.

[0024] Preferably, in step c), the liquid is first lowered at a rate of 14 to 16 mm / s for 1.2 to 1.5 m, then lowered at a rate of 7 to 9 mm / s for 15 to 17 cm, to a distance of 1 to 3 cm from the surface of the perovskite precursor solution, and finally lowered at a rate of 3 to 5 mm / s for 7 to 9 cm, to a distance of 4 to 6 cm from the bottom of the perovskite precursor solution;

[0025] The soaking temperature is 18-26° C., and the soaking time is 60-300 seconds.

[0026] Preferably, in step d), the tube is first raised by 7 to 9 cm at a rate of 1 to 3 mm / s, then by 15 to 17 cm at a rate of 7 to 9 mm / s, and finally by 59 to 61 cm at a rate of 14 to 16 mm / s;

[0027] The annealing temperature is 70-150° C. and the annealing time is 10-30 minutes.

[0028] Preferably, in step d), the component of the perovskite active layer is ABX3;

[0029] A is CH3NH3, NH2CHNH2 or C8H9NH3;

[0030] B is Pb or Sn;

[0031] X is Cl, Br, I or a mixed halide;

[0032] The thickness of the perovskite active layer is 300-600 nm.

[0033] Preferably, when the first charge transport layer is an electron transport layer, the second charge transport layer is a hole transport layer;

[0034] The material of the hole transport layer is NiOx;

[0035] In step e), the parameters for sputtering and depositing the second charge transport layer on the surface of the perovskite active layer include:

[0036] Sputtering power is 500~700W, vacuum degree is <2×10 -3 The flow ratio of Pa, Ar and O2 is 125-25:1, and the sputtering time is 10-20 min;

[0037] In step e), the annealing temperature is 275-350° C. and the time is 20-40 min;

[0038] The thickness of the second charge transport layer is 14-40 nm.

[0039] Preferably, in step f), the conductive electrode is TCO, or the conductive electrode is a multilayer composite transparent conductive electrode formed of metal and TCO;

[0040] The sputtering deposition method is a vertical magnetron sputtering method;

[0041] The parameters for sputtering and depositing a conductive electrode on the surface of the second charge transport layer include:

[0042] Sputtering power is 300~1000W, vacuum degree is <4×10 -4 The flow ratio of Pa, Ar and O2 is 15-105:1, and the sputtering time is 10-30 min;

[0043] The thickness of the conductive electrode is 80-200 nm.

[0044] The present invention also provides a double-sided perovskite solar cell prepared by the preparation method described above.

[0045] The invention provides a method for preparing a double-sided perovskite solar cell, comprising the following steps: a) sputtering and depositing indium tin oxide on both sides of glass to form a double-sided conductive substrate; b) sputtering and depositing a first charge transport layer on both sides of the double-sided conductive substrate; c) first lowering the composite layer group obtained in step b) at a rate of 14-16 mm / s, then lowering at a rate of 7-9 mm / s, and finally immersing it in a perovskite precursor solution at a rate of 3-5 mm / s for immersion; d) lifting the immersed composite layer group out of the perovskite precursor solution in a plane lifting manner, annealing, and forming a perovskite active layer on both sides of the composite layer group; the lifting process comprises: first rising at a rate of 1-3 mm / s, then rising at a rate of 7-9 mm / s, and finally rising at a rate of 14-16 mm / s; e) sputtering and depositing a second charge transport layer on the surface of the perovskite active layer, and annealing; f) sputtering and depositing a conductive electrode on the surface of the obtained second charge transport layer to obtain a double-sided perovskite solar cell. The present invention proposes a method for preparing double-sided perovskite and a transmission layer in one step by step planar lifting. Compared with immersion pulling, the film layer is more uniform. The double-sided perovskite solar cell prepared by the planar lifting method of the present invention has better thickness uniformity, higher power generation and cost saving. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 A structural diagram of a plane lifting device used in one embodiment of the present invention;

[0047] Figure 2 A top view of a glass carrier provided in accordance with an embodiment of the present invention;

[0048] Figure 3 A schematic structural diagram of a double-sided perovskite solar cell provided for one embodiment of the present invention. DETAILED DESCRIPTION

[0049] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0050] The present invention provides a method for preparing a double-sided perovskite solar cell, comprising the following steps:

[0051] a) sputtering indium tin oxide on both sides of the glass to form a double-sided conductive substrate;

[0052] b) sputtering and depositing a first charge transport layer on both sides of the double-sided conductive substrate;

[0053] c) lowering the composite layer group obtained in step b) at a rate of 14 to 16 mm / s, then at a rate of 7 to 9 mm / s, and finally immersing it in a perovskite precursor solution at a rate of 3 to 5 mm / s;

[0054] d) lifting the immersed composite layer group out of the perovskite precursor solution by plane lifting, annealing, and forming perovskite active layers on both sides of the composite layer group;

[0055] The lifting process includes: firstly rising at a rate of 1 to 3 mm / s, then rising at a rate of 7 to 9 mm / s, and finally rising at a rate of 14 to 16 mm / s;

[0056] e) annealing after sputtering and depositing a second charge transport layer on the surface of the perovskite active layer;

[0057] f) sputtering and depositing a conductive electrode on the surface of the obtained second charge transport layer to obtain a double-sided perovskite solar cell.

[0058] The invention firstly sputters and deposits indium tin oxide on both sides of glass to form a double-sided conductive substrate.

[0059] In some embodiments of the present invention, the thickness of the glass is 0.7-2.5 mm. In some embodiments, the thickness of the glass is 2.2 mm.

[0060] In some embodiments of the present invention, the sputtering deposition method is a vertical magnetron sputtering method. In some embodiments, the sputtering deposition is a simultaneous sputtering deposition.

[0061] In some embodiments of the present invention, the parameters for sputtering and depositing indium tin oxide on both sides of glass include:

[0062] Background vacuum degree <4×10 -4 Pa, the target substrate distance is 15-80 cm, the sputtering power is 140-500 W, and the flow ratio of Ar gas to O2 is 30-55:1.

[0063] In some embodiments, the parameters for sputter depositing indium tin oxide on both sides of glass include:

[0064] Background vacuum degree <4×10 -4Pa, the target substrate distance is 30 cm, the sputtering power is 400 W, and the flow ratio of Ar gas to O2 is 35:1.

[0065] In some embodiments of the present invention, the thickness of the indium tin oxide deposition is 120-200 nm. In some embodiments, the thickness of the indium tin oxide deposition is 200 nm.

[0066] In some embodiments of the present invention, the optical transmittance of the double-sided conductive substrate is 80% to 90%, and the resistance is 5 to 20Ω. In some embodiments, the optical transmittance of the double-sided conductive substrate is 89%, and the resistance is 15Ω.

[0067] After obtaining the double-sided conductive substrate, a first charge transport layer is sputter-deposited on both sides of the double-sided conductive substrate.

[0068] In some embodiments of the present invention, the sputtering deposition method is a vertical magnetron sputtering method. In some embodiments, the sputtering deposition is a simultaneous sputtering deposition.

[0069] In some embodiments of the present invention, the first charge transport layer is an electron transport layer or a hole transport layer. The material of the electron transport layer includes TiO2, ZnO or CdS; the material of the hole transport layer is NiOx. In some embodiments, the electron transport layer is a TiO2 electron transport layer.

[0070] In some embodiments of the present invention, the parameters for sputtering and depositing the electron transport layer on both sides of the double-sided conductive substrate include:

[0071] Background vacuum degree <4×10 -4 Pa; the target substrate distance is 10-65 cm, the sputtering power is 100-350 W, and the flow ratio of Ar gas to O2 is 20-75:1.

[0072] In some embodiments, the parameters for sputtering and depositing the electron transport layer on both sides of the double-sided conductive substrate include:

[0073] Background vacuum degree <4×10 -4 Pa; the target substrate distance is 50cm, the sputtering power is 350W, and the flow ratio of Ar gas to O2 is 45:1.

[0074] In some embodiments of the present invention, the thickness of the electron transport layer is 15-50 nm. In some embodiments, the thickness of the electron transport layer is 30 nm.

[0075] After depositing the first charge transport layer, the resulting composite layer group is first lowered at a rate of 14 to 16 mm / s, then lowered at a rate of 7 to 9 mm / s, and finally immersed in the perovskite precursor solution at a rate of 3 to 5 mm / s for soaking.

[0076] In certain embodiments of the present invention, the liquid crystal display device is first descended at a rate of 14 to 16 mm / s for 1.2 to 1.5 m, then descended at a rate of 7 to 9 mm / s for 15 to 17 cm, to a distance of 1 to 3 cm from the surface of the perovskite precursor solution, and finally descended at a rate of 3 to 5 mm / s for 7 to 9 cm, to a distance of 4 to 6 cm from the bottom of the perovskite precursor solution.

[0077] In some embodiments, the tube is first descended at a rate of 15 mm / s for 1.35 m, then descended at a rate of 8 mm / s for 16 cm to a distance of 2 cm from the surface of the perovskite precursor solution, and finally descended at a rate of 4 mm / s for 8 cm to a distance of 5 cm from the bottom of the solution.

[0078] In some embodiments of the present invention, the perovskite precursor solution is prepared according to the following method:

[0079] Lead halide (PbI2), methyl ammonium iodide (MAI) and methyl ammonium chloride (MAICl) are dissolved in a solvent to form a 0.9-1.2 mol / L perovskite material precursor solution. The solvent can be one or more of: NN dimethylformamide (DMF), DMSO, GBL and 2ME.

[0080] In some embodiments, the molar ratio of lead halide (PbI2), methylammonium iodide (MAI) and methylammonium chloride (MAICl) is 0.8-1.2: 0.8-1.2: 0.2-0.5. In some embodiments, the molar ratio of lead halide (PbI2), methylammonium iodide (MAI) and methylammonium chloride (MAICl) is 1:1:0.35.

[0081] In some embodiments, the concentration of the perovskite material precursor solution is 1 mol / L.

[0082] In some embodiments of the present invention, the soaking temperature is 18-26° C., and the soaking time is 60-300 seconds. In some embodiments, the soaking temperature is 25° C., and the soaking time is 200 seconds.

[0083] After the soaking is completed, the soaked composite layer group is lifted out of the perovskite precursor solution by a plane lifting method, and annealed to form perovskite active layers on both sides of the composite layer group.

[0084] The lifting process includes: firstly rising at a rate of 1 to 3 mm / s, then rising at a rate of 7 to 9 mm / s, and finally rising at a rate of 14 to 16 mm / s.

[0085] In certain embodiments of the present invention, the lifting process includes: first rising 7 to 9 cm at a rate of 1 to 3 mm / s, at which time the distance from the surface of the perovskite precursor solution is 1 to 3 cm, then rising 15 to 17 cm at a rate of 7 to 9 mm / s, and finally rising 59 to 61 cm at a rate of 14 to 16 mm / s.

[0086] In some embodiments, the electrode is first raised at a rate of 2 mm / s for 8 cm to a distance of 2 cm from the surface of the perovskite precursor solution; then raised at a rate of 8 mm / s for 16 cm, and finally raised at a rate of 15 mm / s for 60 cm.

[0087] In some embodiments of the present invention, the plane lifting device comprises:

[0088] A glass specimen rack 2; a first connecting device 3-1 connects a first hook 5-1 to the glass specimen rack 2, and a second connecting device 3-2 connects a second hook 5-2 to the glass specimen rack 2;

[0089] A first lifting device 4-1 connected to the first hook 5-1; a second lifting device 4-2 connected to the second hook 5-2; the first lifting device 4-1 and the second lifting device 4-2 drive the glass carrier 2 to rise and fall; during the lifting process, the glass carrier 2 remains horizontal;

[0090] A first motor 6-1 controls the lifting of the first lifting device 4-1, and a second motor 6-2 controls the lifting of the second lifting device 4-2.

[0091] A chemical tank 1 is placed below the glass carrier.

[0092] Figure 1 This is a structural diagram of a plane lifting device used in an embodiment of the present invention. 1 is a chemical tank, 2 is a glass carrier, 3-1 is a first connecting device, 3-2 is a first connecting device, 4-1 is a first lifting device, 4-2 is a second lifting device, 5-1 is a first hook, 5-2 is a second hook, 6-1 is a first motor, 6-2 is a second motor, 7-1 is a first bearing plate, and 7-2 is a second bearing plate.

[0093] In some embodiments of the present invention, the glass carrier comprises:

[0094] Glass plate 2-2;

[0095] Horizontal beams and vertical beams; the horizontal beams include a first horizontal beam 2-4 and a second horizontal beam 2-5; the vertical beams include a first vertical beam 2-6 and a second vertical beam 2-7; a positioning platform 2-3 for positioning the glass plate is provided on the horizontal beams and the vertical beams; screw holes 2-1 are provided on the horizontal beams and the vertical beams; the horizontal beams and the vertical beams are connected by screws.

[0096] Figure 2 A top view of a glass sample rack provided by an embodiment of the present invention, wherein 2-1 is a screw hole, 2-2 is a glass plate, 2-3 is a positioning platform, 2-4 is a first horizontal beam, 2-5 is a second horizontal beam, 2-6 is a first vertical beam, and 2-7 is a second vertical beam.

[0097] In some embodiments of the present invention, the cross beam and the vertical beam are both made of titanium alloy.

[0098] In some embodiments of the present invention, the first connecting device is a metal frame, specifically a heat-treated and strengthened titanium alloy (Ti-6Al-4V). Screw holes are provided on the metal frame, and the metal frame and the crossbeam of the glass carrier are connected by screws.

[0099] In some embodiments of the present invention, the second connecting device is a metal frame, specifically a heat-treated and strengthened titanium alloy (Ti-6Al-4V). Screw holes are provided on the metal frame, and the metal frame and the crossbeam of the glass carrier are connected by screws.

[0100] The present invention has no special limitation on the structure and source of the first hook and the second hook, and they can be common commercially available hooks.

[0101] In some embodiments of the present invention, the first lifting device 4-1 and the second lifting device 4-2 are both fixed pulley assemblies, and the present invention has no special limitation on this. In some embodiments, two fixed pulleys are used in the fixed pulley assembly.

[0102] The present invention has no special limitation on the structure and source of the motor, and the motor may be a general commercially available hook.

[0103] In some embodiments of the present invention, the chemical tank is a box with an upper opening, and the box is a glass box. The present invention has no special restrictions on the size of the box, and it can be selected according to actual needs.

[0104] In some embodiments of the present invention, the lifting device further comprises a first bearing plate 7-1 and a second bearing plate 7-2, wherein the first bearing plate 7-1 is used to place the first motor 6-1, and the second bearing plate 7-2 is used to place the second motor 6-2. In some embodiments, the chemical tank and the first bearing plate are connected by welding; the chemical tank and the second bearing plate are connected by welding. In some embodiments, the material of the bearing plate is titanium alloy. The present invention has no special restrictions on the size of the bearing plate, which can be selected according to actual needs.

[0105] In certain embodiments of the present invention, during the lifting process, the motor and the lifting device do not come into contact with the solution in the chemical tank.

[0106] In some embodiments of the present invention, the annealing temperature is 70-150°C and the time is 10-30 minutes. In some embodiments, the annealing temperature is 100°C and the time is 30 minutes. In some embodiments, the upper and lower surfaces of the composite layer group are annealed simultaneously.

[0107] In certain embodiments of the present invention, the composition of the perovskite active layer is ABX3;

[0108] A is CH3NH3(MA), NH2CHNH2(FA) or C8H9NH3(PEA);

[0109] B is Pb or Sn;

[0110] X is Cl, Br, I or a mixed halide.

[0111] In some embodiments, the component of the perovskite active layer is MAPbI3, specifically, lead halide (PbI2), methyl ammonium iodide (MAI) and methyl ammonium chloride (MAICl) are dissolved in a solvent to form a 0.9-1.2 mol / L perovskite material precursor solution. The solvent can be one or more of: NN dimethylformamide (DMF), DMSO, GBL and 2ME.

[0112] In some embodiments, the molar ratio of lead halide (PbI2), methylammonium iodide (MAI) and methylammonium chloride (MAICl) is 0.8-1.2: 0.8-1.2: 0.2-0.5. In some embodiments, the molar ratio of lead halide (PbI2), methylammonium iodide (MAI) and methylammonium chloride (MAICl) is 1:1:0.35.

[0113] In some embodiments, the concentration of the perovskite material precursor solution is 1 mol / L.

[0114] In some embodiments of the present invention, the thickness of the perovskite active layer is 300-600 nm. In some embodiments, the thickness of the perovskite active layer is 400 nm.

[0115] After the perovskite active layer is obtained, a second charge transport layer is sputter-deposited on the surface of the perovskite active layer, followed by annealing.

[0116] In some embodiments of the present invention, the sputtering deposition method is a vertical magnetron sputtering method. In some embodiments, the sputtering deposition is a simultaneous sputtering deposition.

[0117] In some embodiments of the present invention, when the first charge transport layer is an electron transport layer, the second charge transport layer is a hole transport layer.

[0118] In some embodiments of the present invention, the hole transport layer is made of NiOx.

[0119] In some embodiments of the present invention, the parameters for sputtering and depositing the hole transport layer on the surface of the perovskite active layer include:

[0120] Sputtering power is 500~700W, vacuum degree is <2×10 -3 The flow ratio of Pa, Ar and O2 is 125-25:1, and the sputtering time is 10-20 min.

[0121] In some embodiments, the parameters for sputtering and depositing a hole transport layer on the surface of the perovskite active layer include:

[0122] The sputtering power is 600W and the vacuum degree is <2×10 -3 The flow ratio of Pa, Ar and O2 was 50:1, and the sputtering time was 15 min.

[0123] In some embodiments of the present invention, the annealing temperature is 275-350° C., and the time is 20-40 min. In some embodiments, the annealing temperature is 290° C., and the time is 30 min.

[0124] In some embodiments of the present invention, the thickness of the second charge transport layer is 14-40 nm. In some embodiments, the thickness of the second charge transport layer is 20 nm.

[0125] After annealing, a conductive electrode is sputter-deposited on the surface of the obtained second charge transport layer to obtain a double-sided perovskite solar cell.

[0126] In some embodiments of the present invention, the conductive electrode is TCO, or the conductive electrode is a multi-layer composite transparent conductive electrode formed of metal and TCO.

[0127] In some embodiments of the present invention, the sputtering deposition method is a vertical magnetron sputtering method. In some embodiments, the sputtering deposition is a simultaneous sputtering deposition.

[0128] In some embodiments of the present invention, the parameters for sputtering and depositing a conductive electrode on the surface of the second charge transport layer include:

[0129] Sputtering power is 300~1000W, vacuum degree is <4×10 -4 The flow ratio of Pa, Ar and O2 is 15-105:1, and the sputtering time is 10-30 min.

[0130] In some embodiments, the parameters for sputtering and depositing a conductive electrode on the surface of the second charge transport layer include:

[0131] The sputtering power is 700W and the vacuum degree is <4×10 -4 The flow ratio of Pa, Ar and O2 was 65:1, and the sputtering time was 30 min.

[0132] In some embodiments of the present invention, the thickness of the conductive electrode is 80-200 nm. In some embodiments, the thickness of the conductive electrode is 200 nm.

[0133] The present invention has no particular limitation on the sources of the raw materials used above, and they can be generally commercially available.

[0134] The present invention also provides a double-sided perovskite solar cell prepared by the preparation method described above.

[0135] In some embodiments of the present invention, the double-sided perovskite solar cell comprises:

[0136] Glass;

[0137] Indium tin oxide layers composited on both sides of the glass;

[0138] A first charge transport layer composited on the surface of the indium tin oxide layer;

[0139] A perovskite active layer composited on the surface of the first charge transport layer;

[0140] A second charge transport layer composited on the surface of the perovskite active layer;

[0141] A conductive electrode is composited on the surface of the second charge transport layer.

[0142] Figure 3 A schematic diagram of the structure of a double-sided perovskite solar cell provided by an embodiment of the present invention, wherein C1 is glass, C2 is an indium tin oxide layer, C3 is a first charge transport layer, C4 is a perovskite active layer, C5 is a second charge transport layer, and C6 is a conductive electrode.

[0143] Beneficial effects:

[0144] 1) By using a one-step planar lifting method rather than a longitudinal pulling method, the thickness non-uniformity of the perovskite layer is reduced to 3500cm 2 For large-area modules, the percentage dropped from 18.9% to 12.4%;

[0145] 2) Plane lifting through 3-step deceleration and 3-step acceleration method, so that the thickness of the perovskite layer is uniform at 3500cm 2 On large-area modules, the percentage dropped from 12.4 to 6.7%.

[0146] 3) Redesign the plane lifting equipment, this equipment has the following advantages:

[0147] Different screw holes can be connected by screws to prepare perovskite photovoltaic modules of different sizes, so that the area can be flexibly adjusted without preparing different carriers for different areas.

[0148] By introducing a motor to drive the lifting device to lift up and down, and placing the motor and the lifting device outside the chemical tank, it is possible to avoid the adsorption of chemical solutions on the lifting device, thereby increasing the lifespan and precise control;

[0149] By directly welding the bearing plate under the motor to the chemical tank, movement during chemical immersion and lifting can be avoided to affect the uniformity of film thickness.

[0150] In order to further illustrate the present invention, a double-sided perovskite solar cell and a preparation method thereof provided by the present invention are described in detail below in conjunction with embodiments, but it should not be understood as limiting the scope of protection of the present invention.

[0151] The reagents used in the following examples are all commercially available.

[0152] The IV efficiency tests of the cells prepared in Comparative Examples 1 to 4 and Example 1 were carried out in the following manner: The IV curve and steady-state Jsc were tested by a solar simulator (7SS1503A, Beijing, simulating AM1.5G sunlight with a light intensity of 100 mW / cm 2 , using a digital source meter 2600KeithleyInstruments Inc) to record data; the incident light intensity was calibrated with a silicon solar cell F calibrated by NREL (Newport Stratford Inc 91150V); the scan rate was 50mV / s, the delay time was 0.1s; the reverse scan was from 80V to 0.05V, and the forward scan was from 0.05V to 80V.

[0153] The thickness uniformity was tested using a step profiler. Nine points on the glass substrate were taken on average for film thickness testing. The thickness uniformity was: (maximum value - minimum value) / average value × 100%.

[0154] Example 1

[0155] Preparation of double-sided perovskite solar cells:

[0156] 1) Using vertical magnetron sputtering method, ITO is sputtered and deposited on both sides of 2.2 mm thick glass to form a double-sided conductive substrate;

[0157] The parameters for sputter depositing ITO on both sides of glass include:

[0158] Background vacuum degree <4×10-4 Pa, the target-substrate distance was 30 cm, the sputtering power was 400 W, and the flow ratio of Ar gas to O2 was 35:1;

[0159] The thickness of the indium tin oxide deposition is 200 nm;

[0160] The optical transmittance of the double-sided conductive substrate is 89% and the resistance is 15Ω;

[0161] 2) Using a vertical magnetron sputtering method, a TiO2 electron transport layer is simultaneously sputtered and deposited on both sides of the double-sided conductive substrate; the parameters of the sputtering deposition include:

[0162] Background vacuum degree <4×10 -4 Pa; the target-substrate distance is 50 cm, the sputtering power is 350 W, and the flow ratio of Ar gas to O2 is 45:1;

[0163] The thickness of the electron transport layer is 30 nm;

[0164] 3) The composite layer group obtained in step 2) was first lowered for 1.35 m at a rate of 15 mm / s, then lowered for 16 cm at a rate of 8 mm / s, until the distance to the surface of the perovskite precursor solution was 2 cm, and finally lowered for 8 cm at a rate of 4 mm / s until the distance to the bottom of the solution was 5 cm, and immersed at 25° C. for 200 s;

[0165] 4) lifting the immersed composite layer group out of the perovskite material precursor solution by plane lifting, annealing, and forming a perovskite active layer (with a component of MAPbI3) on both sides of the composite layer group;

[0166] The perovskite material precursor solution is prepared according to the following method:

[0167] Lead halide (PbI2), methylammonium iodide (MAI) and methylammonium chloride (MAICl) were dissolved in DMF solvent at a molar ratio of 1:1:0.35 to form a 1 mol / L perovskite precursor solution;

[0168] The lifting process includes: firstly, rising 8 cm at a rate of 2 mm / s, at which time the distance from the surface of the perovskite precursor solution is 2 cm; then rising 16 cm at a rate of 8 mm / s, and finally rising 60 cm at a rate of 15 mm / s;

[0169] The lifting is carried out as follows Figure 1 The lifting device shown in the figure; the glass carrier in the lifting device is as follows Figure 2 As shown;

[0170] Then, the substrate is transferred to an annealing chamber and annealed on both the upper and lower surfaces at the same time; the annealing temperature is 100° C. and the time is 30 minutes;

[0171] The thickness of the perovskite active layer is 400 nm;

[0172] 5) sputtering and depositing a NiOx hole transport layer on the surface of the perovskite active layer by a vertical magnetron sputtering method, followed by annealing;

[0173] The parameters for sputtering the NiOx hole transport layer include:

[0174] The sputtering power is 600W and the vacuum degree is <2×10 -3 The flow ratio of Pa, Ar and O2 was 50:1, and the sputtering time was 15 min;

[0175] The annealing temperature is 290°C and the annealing time is 30 minutes;

[0176] The thickness of the NiOx hole transport layer is 20 nm;

[0177] 6) using a vertical magnetron sputtering method to sputter-deposit a conductive electrode TCO on the surface of the NiOx hole transport layer to obtain a double-sided perovskite solar cell;

[0178] The parameters for sputtering deposited conductive electrode TCO include:

[0179] The sputtering power is 700W and the vacuum degree is <4×10 -4 The flow ratio of Pa, Ar and O2 was 65:1, and the sputtering time was 30 min;

[0180] The thickness of the conductive electrode is 200 nm.

[0181] The performance of the obtained double-sided perovskite solar cell was tested, and the experimental results showed that the thickness uniformity of the double-sided perovskite solar cell was 89%, and the photoelectric conversion efficiency of the double-sided perovskite solar cell was 30W.

[0182] Comparative Example 1

[0183] Modify step 3 of Example 1 to:

[0184] The composite layer group obtained in step 2) is lowered to 5 cm from the bottom of the solution at a rate of 2 mm / s, and immersed at 25° C. for 250 s;

[0185] The remaining steps are the same as those in Example 1 to produce a double-sided perovskite solar cell.

[0186] The performance of the obtained double-sided perovskite solar cell was tested, and the experimental results showed that the thickness uniformity of the double-sided perovskite solar cell was 87%, and the photoelectric conversion efficiency of the double-sided perovskite solar cell was 28.7W.

[0187] Comparative Example 2

[0188] The lifting process of step 4) of Example 1 is modified as follows:

[0189] Directly rise at a rate of 8 mm / s for 200 s;

[0190] The remaining steps are the same as those in Example 1 to produce a double-sided perovskite solar cell.

[0191] The performance of the obtained double-sided perovskite solar cell was tested, and the experimental results showed that the thickness uniformity of the double-sided perovskite solar cell was 69%, and the photoelectric conversion efficiency of the double-sided perovskite solar cell was 21.5W.

[0192] Comparative Example 3

[0193] Modify step 3) and step 4) of Example 1 into the steps of the Czochralski method:

[0194] Vertically pull down at a speed of 5 mm / s to 2 cm from the bottom of the solution, soak at 25°C for 250 s, and then vertically pull up at a speed of 5 mm / s for 300 s;

[0195] The remaining steps are the same as those in Example 1 to produce a double-sided perovskite solar cell.

[0196] The performance of the obtained double-sided perovskite solar cell was tested, and the experimental results showed that the thickness uniformity of the double-sided perovskite solar cell was 58%, and the photoelectric conversion efficiency of the double-sided perovskite solar cell was 17.6W.

[0197] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a double-sided perovskite solar cell, comprising the following steps: a) sputtering indium tin oxide on both sides of the glass to form a double-sided conductive substrate; b) sputtering and depositing a first charge transport layer on both sides of the double-sided conductive substrate; c) lowering the composite layer group obtained in step b) at a rate of 14 to 16 mm / s, then at a rate of 7 to 9 mm / s, and finally immersing it in a perovskite precursor solution at a rate of 3 to 5 mm / s; d) lifting the immersed composite layer group out of the perovskite precursor solution by plane lifting, annealing, and forming perovskite active layers on both sides of the composite layer group; The lifting process includes: firstly rising at a rate of 1 to 3 mm / s, then rising at a rate of 7 to 9 mm / s, and finally rising at a rate of 14 to 16 mm / s; e) annealing after sputtering and depositing a second charge transport layer on the surface of the perovskite active layer; f) sputtering and depositing a conductive electrode on the surface of the obtained second charge transport layer to obtain a double-sided perovskite solar cell.

2. The preparation method according to claim 1, characterized in that: In step a), the sputtering deposition method is a vertical magnetron sputtering method; The parameters for sputter depositing ITO on both sides of glass include: Background vacuum degree <4×10 -4 Pa, target-substrate distance is 15-80 cm, sputtering power is 140-500 W, and the flow ratio of Ar gas to O2 is 30-55:1; The thickness of the indium tin oxide deposition is 120 to 200 nm; The optical transmittance of the double-sided conductive substrate is 80% to 90%, and the resistance is 5 to 20Ω.

3. The preparation method according to claim 1, characterized in that: In step b), the sputtering deposition method is a vertical magnetron sputtering method; The first charge transport layer is an electron transport layer or a hole transport layer; The material of the electron transport layer includes TiO2, ZnO or CdS; The hole transport layer is made of NiOx.

4. The preparation method according to claim 3, characterized in that: Parameters for sputtering and depositing the electron transport layer on both sides of the double-sided conductive substrate include: Background vacuum degree <4×10 -4 Pa; target-substrate distance is 10-65 cm, sputtering power is 100-350 W, flow ratio of Ar gas to O2 is 20-75:1; The thickness of the electron transport layer is 15-50 nm.

5. The preparation method according to claim 1, characterized in that: In step c), the tube is first lowered at a rate of 14 to 16 mm / s for 1.2 to 1.5 m, then lowered at a rate of 7 to 9 mm / s for 15 to 17 cm, to a distance of 1 to 3 cm from the surface of the perovskite precursor solution, and finally lowered at a rate of 3 to 5 mm / s for 7 to 9 cm, to a distance of 4 to 6 cm from the bottom of the perovskite precursor solution; The soaking temperature is 18-26° C., and the soaking time is 60-300 seconds.

6. The preparation method according to claim 1, characterized in that: In step d), the tube is first raised at a rate of 1 to 3 mm / s for 7 to 9 cm, then at a rate of 7 to 9 mm / s for 15 to 17 cm, and finally at a rate of 14 to 16 mm / s for 59 to 61 cm; The annealing temperature is 70-150° C. and the annealing time is 10-30 minutes.

7. The preparation method according to claim 1, characterized in that: In step d), the component of the perovskite active layer is ABX3; A is CH3NH3, NH2CHNH2 or C8H9NH3; B is Pb or Sn; X is Cl, Br, I or a mixed halide; The thickness of the perovskite active layer is 300-600 nm.

8. The preparation method according to claim 1, characterized in that: When the first charge transport layer is an electron transport layer, the second charge transport layer is a hole transport layer; The material of the hole transport layer is NiOx; In step e), the parameters for sputtering and depositing the second charge transport layer on the surface of the perovskite active layer include: Sputtering power is 500~700W, vacuum degree is <2×10 -3 The flow ratio of Pa, Ar and O2 is 125-25:1, and the sputtering time is 10-20 min; In step e), the annealing temperature is 275-350° C. and the time is 20-40 min; The thickness of the second charge transport layer is 14-40 nm.

9. The preparation method according to claim 1, characterized in that: In step f), the conductive electrode is TCO, or the conductive electrode is a multilayer composite transparent conductive electrode formed by metal and TCO; The sputtering deposition method is a vertical magnetron sputtering method; The parameters for sputtering and depositing a conductive electrode on the surface of the second charge transport layer include: Sputtering power is 300~1000W, vacuum degree is <4×10 -4 The flow ratio of Pa, Ar and O2 is 15-105:1, and the sputtering time is 10-30 min; The thickness of the conductive electrode is 80-200 nm.

10. A double-sided perovskite solar cell prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Novel organic-inorganic hybrid transparent conductive film and preparation method thereof

    CN101037509A

  • Preparation method of cadmium-free copper indium gallium selenide thin-film solar cells and their zinc sulfide buffer layer films

    CN102270699A